A systematic review of worldwide data on tinea capitis: analysis of the last 20 years. (17th November 2020) - Rodríguez‐Cerdeira, C.; Martínez‐Herrera, E.; Szepietowski, J.C.; Pinto‐Almazán, R.; Frías‐De‐León, M.G.; Espinosa‐Hernández, V.M.; Chávez‐Gutiérrez, E.; García‐Salazar, E.; Vega‐Sánchez, D.C.; Arenas, R.; Hay, R.; Saunte, D.M.
Abstract: Dermatophyte infections are the most common fungal infections in humans; among them, tinea capitis (TC) – the most contagious fungal infection – is caused by anthropophilic, zoophilic and geophilic dermatophytes. The purpose of this systematic review was to determine the different aetiological variants involved in TC and the overall epidemiology of the causes of this infection in the last two decades. We searched the MEDLINE (PubMed) and Embase databases for articles published from July 2000 to August 2019 using the following search terms: 'Tinea capitis', 'Africa', 'America', 'Asia', 'Europe', 'Oceania', and the names of the countries on each continent. The flow of information through the different phases in this systematic review was depicted using a PRISMA flow diagram, which mapped the number of records identified, included and excluded, and the reasons for exclusion. Our findings indicate that the frequency of different aetiologic agents of TC in the reported studies varied globally, from 0.4–87.7% in Africa, 0.2–74.0% in North America, 0.0–91.2% in Eastern Asia, 0.0–69.0% in Eastern Europe and 2.9–86.4% in Oceania. Microsporum canis is the most frequent reported zoophilic agent worldwide, while Trichophyton violaceum and Trichophyton tonsurans are the predominant anthropophilic agents. Over time, the frequency of these latter fungal infections has increased globally, and these fungi have become the major species globally. Anthropophilic transmission – the most prevalent type of transmission – could be explained by two factors: (i) the socioeconomic status of affected countries and population groups with associated risk factors and (ii) movement of populations importing new causes of infection to areas where they had not been encountered previously. We observed that intercontinental migration and travel; globalization; environmental, climatic and ecological changes; and accelerated evolution of health technologies may influence the observed epidemiological changes and, consequently, contributed to the variations in the global status of TC.